Discourse/Counter-Discourse : The Theory and Practice of Symbolic Resistance in Nineteenth-Century France - Terdiman, Richard (Book collections on Project MUSE., 1985)
Discourse/Counter-Discourse is situated on the border between cultural history and literary criticism: combining the insights of Marxism and semiotics, it attempts to delineate the cultural function of texts. Focusing on France during a period of remarkable cultural, social, and political transformation, Richard Terdiman examines both the dominant bourgeois discourse-novels, newspapers, and other mass forms of expression-and the effort of intellectuals to devise counter-discourses to combat it.